MERANCANG PEMBELAJARAN BAHASA INGGRIS BERBASIS PENDEKATAN ISLAMI - Riza Amelia (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
Affective teaching is fundamental in education process. It aims at developing excellent moral output. For Muslims, values of Islam cover all aspects of life. Therefore Islamic education is necessarily integrated into all instructional contents so students can fully develop their attitude accordingly. English is a necessary subject, but on the other hand, it also teaches the idea of secularity which exist in English culture. Integrating Islamic values can be done through: (1) add exercises that reflect Islamic values in the topic being taught; (2) insert Islamic names for people, place, or events in the exercises; (3) enclose relevant Al-Qur’an and/or hadits; and (4) mix some Islamic expressions related to the given topic